How to read a modern painting : understanding and enjoying the modern masters - Thompson, Jon, 1936-2016 (New York : Abrams, 2006)
Modern art, filled with complex themes and subtle characteristics, is a wonder to view, but can be intimidating for the casual observer to comprehend. In this accessible, practical guide, author and instructor Jon Thompson explores more than 200 works, helping readers to unlock each painting's meaning. Beginning with the Barbizon school and the Realist movement of the mid-19th century and continuing through the 1980s avant-garde, artists including Bonnard, Basquiat, Van Gogh, Picasso, Degas, Warhol, and Whistler are featured. Thompson describes each artist's use of media and symbolism and provides insightful biographical information. A natural companion to Abrams' "How to Read a Painting," this book is a vibrant, informative trip through one of art history's most compelling periods.
Includes bibliographical references (pages 379-380) and index.
Keywords: Painting, Modern -- 19th century; Painting, Modern -- 20th century; Art appreciation